2006
DOI: 10.1124/mol.106.028126
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genetic Diversity in the High-Affinity Carnitine Transporter OCTN2 (SLC22A5)

Abstract: Systemic carnitine deficiency (SCD) is a rare autosomal recessive disease resulting from defects in the OCTN2 (SLC22A5) gene, which encodes the high-affinity plasma membrane carnitine transporter. Although OCTN2 is fairly well studied in its relationship with SCD, little is known about the carrier frequency of disease-causing alleles of OCTN2, or of more common functional polymorphisms in this gene. To address these issues, we screened for genetic variants in the OCTN2 coding region by direct sequencing of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 38 publications
(51 reference statements)
3
32
1
2
Order By: Relevance
“…2B). These results agree with previous expression studies in HEK 293 cells [23] and in CHO cells [19]. Statistical analysis indicated that heterozygosity for primary carnitine deficiency was not a risk factor for cardiomyopathy (odds ratio=0.55 with a 95% confidence interval of 0.09 to 3.33, i.e.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…2B). These results agree with previous expression studies in HEK 293 cells [23] and in CHO cells [19]. Statistical analysis indicated that heterozygosity for primary carnitine deficiency was not a risk factor for cardiomyopathy (odds ratio=0.55 with a 95% confidence interval of 0.09 to 3.33, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…With this assumption, only 2/324 patients with cardiomyopathy were heterozygous for mutations in the carnitine transporter gene. This compares with a rate of 0.5-1% in the general population estimated from the 1:40,000-1:120,000 prevalence of primary carnitine deficiency [3][4][5] and with a frequency of 1.11% obtained from the analysis of 270 normal controls [23] and our expression studies of the changes identified (Fig. 2B).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…DNA was collected from 842 unrelated individuals in the San Francisco Bay Area as part of the Studies of Pharmacogenetics in Ethnically Diverse Populations (SOPHIE) project (32). Subjects identified themselves as African American, Caucasian American, Chinese American, or Mexican American by having all four grandparents of the stated ethnicity.…”
Section: Methodsmentioning
confidence: 99%